Social policy and the capability approach : concepts, measurements and application - Yerkes, Mara; Javornik, Jana; Kurowska, Anna (Bristol University Press ; Policy Press, 2019)
This book explores the advantages of the capability approach and offers a way forward in addressing conceptual and empirical issues as they apply specifically to social policy research and practice.